Seasonal variation in mortality in Brazil - Almeida, Victor Foscarini (2024)
Epidemiological studies frequently focus on mortality to understand its distribution and determinants, enabling public health professionals and policymakers to formulate more effective short-term actions and long-term policies. Researchers worldwide have observed a seasonal variation in mortality that varies geographically, with a noteworthy excess of winter death in temperate regions. However, comparative large-scale studies remain limited, particularly outside temperate climates and European contexts. The challenge of measuring and comparing seasonality across regions is exacerbated by differing methodologies and seasonality metrics used in various studies, along with varying data availability. Given Brazil\'s heterogeneous socioeconomic and climatic conditions coupled with a homogeneous healthcare database, it presents an optimal setting for studying the seasonal variation in mortality. We examined over 22 million mortality records between 2000 and 2019 from Brazil\'s healthcare database, classified by cause according to ICD-10 codes. Our analysis assessed common seasonality indexes and introduced a novel metric called the Excess Death index (EDi) that accounts for the possibility that the excess death period might happen in a period different from the winter and, therefore, adapts well across diverse climatic contexts, from temperate to equatorial, while still retaining a simplicity that makes it easily reproducible. We further explored the relationship between climate variables and mortality seasonality. Our study uncovers previously unobserved seasonal mortality patterns throughout Brazil, indicating considerable seasonality even in the tropical and equatorial northern regions. Those patterns, influenced by similar causes of death observed in the southern regions, are less pronounced and differently timed in the north. Additionally, our findings provide insights into the most critical climate variables associated with mortality, highlighting Dew Point Temperature as a paramount factor.